The IIUM: towards a research-intensive university - Nordin, Mohamad Sahari; Syed Abdullah Idid, Syed Arabi (IIUM Press, 2009)
Introduction: This chapter gives an overview of the development of research at the International Islamic University Malaysia (IIUM). It chronicles key milestones that led to the evolution of the university's research activities and practices, and outlines the IIUM's areas of research focus, research trends and sources of research funding, with a particular emphasis on the experience of its Research Management Centre (RMC). Finally, the chapter presents several success stories along with prevailing issues and challenges confronting research and development at the IIUM.